Dominant attributes of administrative delict - Kolpakov, Valeriy K. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article discusses the dominant (main) characteristics of administrative violations of law (administrative tort). The author explores the concept, features, types, a set of basic elements (attributes) of which is an administrative offense. He classifies them: a) the degree of public danger; b) the nature of the harm caused; c) guilty subjects; g) the structure; e) the regulation of the law. Proves that the collection of basic elements (attributes) form a system of administrative offense.